Revisiting the richness of integrated vehicle and crew scheduling - Liping Ge; Natalia Kliewer; Abtin Nourmohammadzadeh; Stefan Voß; Lin Xie (Public Transport, 2022)
The last decades have seen a considerable move forward regarding integrated vehicle and crew scheduling in various realms (airline industry, public transport). With the continuous improvement of information and communication technology as well as general solvers it has become possible to formulate more and more rich versions of these problems. In public transport, issues like rostering, delay propagation or days-off patterns have become part of these integrated problems. In this paper we aim to revisit an earlier formulation incorporating days-off patterns and investigate whether solvability with standard solvers has now become possible and to which extent the incorporation of other aspects can make the problem setting more rich and still keep the possible solvability in mind. This includes especially issues like delay propagation where in public transport delay propagation usually refers to secondary delays following a (primary) disturbance. Moreover, we investigate a robust version to support the claim that added richness is possible. Numerical results are provided to underline the envisaged advances.
Keywords: 380; Operations Research/Decision Theory; Automotive Engineering; Computer-Aided Engineering (CAD; CAE) and Design; Transportation